Perbandingan Daya Guna Kombinasi Ondansetron 4mg dan Dexamethasone 8mg dengan Granisetron 3mg dalam Mencegah Mual Muntah pada Pasien Berisiko Tinggi Pascaoperasi Traktus Gastrointestinal - Mahardieni, Karlina; Wisudarti, Calcarina Fitriani Retno; Sari, Djayanti (Jurnal Komplikasi Anestesi, 2018)
Background. PONV is one of the side effects that often occur after general anesthesia, occurs in the first 24 hours post surgery and occurs in as many as 30 - 70 % of hospitalized patients. PONV greatly avoided by patients and anesthesiologists. Objective. To compare the efficacy of ondansetron 4mg IV-dexamethasone 8mg IV combination with granisetron 3mg IV for preventing of postoperative nausea and vomiting (PONV) in high risk patient in gastrointestinal tract operation. Methods. The research design was randomized control trial (RCT) study with the total of 80 patients, aged 18-60 years old, physical status ASA I and II who underdue gastrointestinal tract operation recruited. Data analysis is done by determined PONV score, side effect, rescue antiemetic needed, incidence and severity of PONV, fentanyl and neostigmine added, fluid status and duration of operation. Results. Incidence PONV of ondansetron-dexamethasone group is 12,5%. Incidence PONV of granisetron group is 10%. There was no significant difference of incidence PONV between these groups. In this study there was no side effect between these groups. Conclusions. Efficacy of ondansetron 4mg IV-dexamethasone 8mg IV combination with granisetron 3mg IV for preventing of postoperative nausea and vomiting (PONV) in high risk patient in gastrointestinal tract operation was no significant difference.